Changing patterns of habitat use by southern right whales (Eubalaena australis) on their nursery ground at Península Valdés, Argentina, and in their long-range movements - Rowntree, Victoria J.; Payne, Roger S.; Schell, Donald M. (J. Cetacean Res. Manage., 2020)
Southern right whales (Eubalaena australis) have been studied on their nursery ground at Península Valdés, Argentina, every year since 1970. Since 1990, 1,208 individuals have been identified from photographs taken during annual aerial surveys; 618 whales were seen in two or more years. Patterns of habitat use have changed during the study in ways which suggest that right whales may be capable of substantial behavioral and ecological flexibility. One male and three females from Península Valdés have been sighted on other nursery grounds (Tristan da Cunha and southern Brazil). Three individuals from Península Valdés were sighted on feeding grounds off Shag Rocks and South Georgia. Some right whales from Península Valdés showed carbon and nitrogen isotope ratios very similar to those seen in right whales off South Africa, while others showed distinctive isotope ratios indicating that they fed in a different area. Whales of all ages and both sexes moved frequently between three major regions of concentration on the Península Valdés nursery ground. Subadults and adult females with calves were resighted at higher rates than adult males and females in non-calf years. Changes in the geographic distribution of whales at the Península include: (1) abandonment of a major region of concentration; (2) establishment of a nursery area adjacent to the centre of a growing whalewatching industry; and (3) small-scale shifts in distribution, possibly in response to natural and human disturbances.